The Effect of Incorporating an Exergame Application in a Multidisciplinary Weight Management Program on Physical Activity and Fitness Indices in Children with Overweight and Obesity - Rotem Kahana; Shai Kremer; Merav Dekel Dahari; Einat Kodesh (MDPI AG, 2021)
Children with overweight/obese (OW/OB) have low physical activity (PA) levels and excessive daily screen times. Although access to personal smartphones may complicate restricting sedentary screen time, these devices may be used to promote PA and improve fitness. Therefore, we aim to examine the impact of incorporating an exergame application (APP) into an existing weight management program on BMI, physical activity, fitness levels, and attitude toward PA among OW/OB children. Seventy-nine children (51% girls), median age 10 years, completed an established 5-month weight management program. The intervention included structured PA sessions (2/week), nutritional, and behavioral counseling. An exergame app was installed on the smartphones of the intervention group (APP, n = 32). BMI, physical fitness, PA level, and attitudes toward PA were assessed before and after the intervention. BMI decreased (p < 0.0001) in both groups by 0.67 kg/m2 (Q1, Q3: −1.36-0.12). There were improvements in more fitness components in the APP group than controls, with significantly greater improvements in aerobic fitness (p = 0.038), speed and agility (p = 0.01), and leg strength endurance (p = 0.05) compared to controls. PA levels increased similarly in both groups during the intervention period. The incorporation of an exergame application leads to more significant improvements in fitness components. These findings support the use of exergame apps to improve fitness in OW/OB children.